The Effect of Problem Based Instruction Model Based on Learning Video and Educational Games Media on the Self Efficacy of Students of Class X SMK N 17 Jakarta - Gabriella Jessi Sitohang; Ati Sumiati; Santi Susanti (Journal Corner of Education, Linguistics, and Literature, 2021)
This study discusses the differences in self-efficacy of class X students at SMK N 17 Jakarta from the application of the PBI learning model with the help of two different learning media. The media used in this research are learning videos which applied to the experimental class and educational games (quizizz) in the control class. The limitations of the problem in this study include, the broad scope only includes information obtained from the results of the application of the PBI learning model with two different media on student self-efficacy, the information presented, includes : application of the PBI learning model with learning video media and educational games, differences in student self-efficacy. The purpose of the study was to find evidence of whether there was a difference in student self-efficacy after the implementation of the PBI learning model with the help of two different media. Based on the data hypothesis test conducted by comparing the scores of the self-efficacy between the experimental class and the control class, it was concluded that there was a significant difference between the students' self-efficacy in both classes. The average score of self-efficacy in the experimental class is higher than the control class, so that in the future the use of learning video media can be one of the best alternative during the implementation of PBI learning model to support student self-efficacy.